Unmet healthcare needs in homeless women with children in the Greater Paris area in France. - Cécile Vuillermoz; Stéphanie Vandentorren; Ruben Brondeel; Pierre Chauvin (PLoS ONE)
Background Despite their poor health status, homeless women encounter many barriers to care. The objectives of our study were to estimate the prevalence of unmet healthcare needs in homeless women and to analyse associated relationships with the following factors: financial and spatial access to care, housing history, migration status, healthcare utilisation, victimization history, caring for children, social network and self-perceived health status. Methods We used data from 656 homeless women interviewed during the ENFAMS representative survey of sheltered homeless families, conducted in the Paris region in 2013. Structural equation models (SEM) were used to estimate the impact of various factors on homeless women's unmet healthcare needs. Results Among those interviewed, 25.1% (95%CI[21.3-29.0]) had at least one unmet healthcare need over the previous year. Most had given up on visiting general practitioners and medical specialists. No association with factors related to financial access or to health insurance status was found. However, food insecurity, poor spatial health access and poor self-perceived health were associated with unmet healthcare needs. Self-perceived health appeared to be affected by victimization and depression. Discussion The lower prevalence of unmet healthcare needs in homeless women compared with women in stable housing situations suggests that homeless women have lower needs perceptions and/or lower expectations of the healthcare system. This hypothesis is supported by the results from SEM. Strategies to provide better access to care for this population should not only focus on financial interventions but also more broadly on spatial healthcare access, cultural norms, and perceptions of health. Reducing their unmet needs and improving their access to healthcare and prevention must include an improvement in their living, financial and housing conditions.